Digital Leadership In Managing Public Organization Indonesia - Fitriani,; Ransta L Lekatompessy,; Hesty Tambajong,; Fransin Kontu,; Imelda C Laode,; Umiyati Haris,; Welhelmina Jeujanan, (Technium Social Sciences Journal, 2023)
The development of information and communication technology (ICT) has brought fundamental changes in the world of public organizations. This study aims to analyze the role and impact of digital leadership in managing public organizations in the digital era. The research method used is a qualitative approach using case studies from several public organizations that have implemented digital leadership. Data was collected through in-depth interviews with government officials, managers and staff of organizations involved in digital transformation. The results of the study show that digital leadership functions as a catalyst in facing the challenges of rapid change in the digital era. Digital leadership encourages public organizations to adopt and apply relevant information technologies, and enhance digital skills and literacy at all levels. In addition, digital leadership also creates a culture of innovation and collaboration within public organizations. The digital leader encourages the active participation of staff and members of the organization in creating technology-based solutions to improve the quality of public services and operational efficiency. During the digital transformation process, digital leadership also focuses on managing change and overcoming emerging obstacles. Digital leaders have an important role to play in unifying the vision and building commitment to digital transformation, as well as helping to overcome resistance from those who are less familiar with new technologies. However, this research also identifies several challenges in implementing digital leadership in public organizations. Some of these are the lack of adequate resources and budget, and the need to address concerns regarding data security and privacy. In conclusion, digital leadership has proven itself as a key factor in managing public organizations in the digital era. Digital transformation led by digital leaders brings positive changes in efficiency, transparency and citizen participation in public services. To address these challenges, governments and public organizations need to invest in human resource training and development, and design policies and strategies that support technological innovation and adaptation to achieve success in digital leadership.